EFEKTIVITAS KOMBINASI PLASMA JET NON -THERMAL DAN SPRAY Aloe vera (L). Burm. f . PADA PENYEMBUHAN LUKA DIABETES - Ratih Arum Astuti; Laela Hayu Nurani; Eka Wahyuning Tyas; Iis Wahyuningsih; Devi Kumala Dewi; Isabella Meliawati Sikumbang; Nasruddin Nasruddin (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Plasma jet non thermal has benefit in wound healing, but less control can to accumulation of reactive oxygen species. This study aims to determine the effectiveness of the combination of plasma jet and A. vera spray 1% for wound healing in diabetic wounds mice model with parameters of malondialdehyde levels, the skin wound ratio, and blood profile. This study used male Balb/C were induced by a streptozotocin (STZ) and divided into 4 groups, namely groups of untreated diabetic mice wounds (N), groups of diabetic mice wound with A. vera spray 1% (Av), groups of diabetic mice wound with plasma jet non thermal at distance of 20 mm for 3 minutes (P), and groups of diabetic mice wound with plasma jet non thermal at distance of 20 mm for 3 minutes and A. vera spray 1% (PAv). The solution of A. vera spray 1% preparation consists of A. vera, DMSO, and aquabidest extracts. The wounds of all groups treated for 14 days then the malondialdehyde, skin wound ratio and blood profile were calculated by SPSS Statistic. The results of blood glucose before treatment were 241.74 dL Ã‚Â± 51.99. The combination of plasma jet and A. vera spray 1% groups were significant (p <0.05) in reduce malondialdehyde levels, reduced the the skin wound ratio but not different significantly (p> 0.05), and not effect on blood profile data (p> 0.05). In conclusion, A. vera spray 1% can reduce the side effects of plasma jet in diabetic wounds by reducing malondialdehyde levels.